Chyluria after Partial Nephrectomy: Case Report and Review of the Literature - Ronald J. Kim; Fadi N. Joudi (The Scientific World Journal)
We report a case of 61-year-old male who presented with chyluria after partial nephrectomy. During workup for appendicitis, an incidental exophytic renal mass was revealed on CT scan. The patient ultimately underwent uncomplicated open partial nephrectomy. Postoperatively, his JP drain output turned milky white with urine remaining clear. JP fluid analysis was consistent with lymph. At 3 weeks postsurgery, his drain output decreased, but his urine turned milky white. Urinalysis confirmed fat in the urine. CT imaging revealed chyloma/urinoma with extravasation. The patient was initially treated conservatively, with a medium-chain fatty acid diet and then ureteral stenting. His stent was eventually removed and his chlyuria resolved 14 weeks later.